Citizen’s Participation as Co-Producer in Licensing - Teuku Muhamad Rizki Ramadhan; Vishnu Juwono (Publik : (Jurnal Ilmu Administrasi), 2021)
. To improve the image of the bureaucracy, which is still complicated and difficult, causing the public's reluctance to take care of their own permits, the one-stop integrated service and investment office (DPMPTSP) Province of DKI Jakarta initiated the implementation of the PTSP Keliling Kampung as part of the PTSP Ruang Publik Program. The activity was carried out using the Co-Production concept which includes the role of citizens’ participation in it. The purpose of this study is to see the extent of citizen’s participation as co-producer in licensing service activities through co-production forming factors and involvement in each phase of the service cycle. This research was conducted through a post-positivist approach with qualitative data collection methods. The results of the study show that in these activities community participation as co-producers has been seen with the active involvement of the community in the form of providing resources in service activities and licensing assistance, the motivation of the community as a voluntary public service provider, and the creation of private and/or public value in the form of outputs or outcomes. Seeing community involvement in the service cycle phase, including in the commissioning, designing, delivery, and assessment phases, in these activities community participation as co-producers has reached the assessment phase. This activity has achieved social benefits and the active role of the co-producer starting from the planning stage to the evaluation and assessment stage in the licensing service activity.